A STUDY ON MARKETPLACES AND THEIR TOOLS - Araújo, Liriane Soares; Ferreira, Cassio (Revista Interface Tecnológica, 2024)
Marketplaces have become a focal point of interest since the 1990s, combining innovative technology with interorganizational information systems. This study explores the use of marketplaces such as Mercado Livre, Magalu, Amazon, B2W, Shopee, and Shein, highlighting their advantages and challenges. Along with marketing strategies, sales policies, and customer support, a case study is conducted on Armário Infantil, a children’s clothing company from Catanduva-SP. The study aims to provide insights to optimize e-commerce operations, emphasizing the use of the ERP system Bling, exploring the evolution of marketplaces, the need for management tools like Bling, and the implications of efficient integration for business processes. The methodology used includes both quantitative and qualitative interviews and analyses, focusing on the implementations carried out at Armário Infantil. The research reveals improvements in inventory management and increased sales, particularly on platforms such as Shopee and Mercado Livre, despite persistent challenges like stock integration and maintaining sales growth. The study aims to present practices that can optimize the benefits of marketplaces and offer recommendations for continued adjustments to sustain the company’s success in the online market.